2021
DOI: 10.3390/ijms22158026
|View full text |Cite
|
Sign up to set email alerts
|

Organ Specific Differences in Alteration of Aquaporin Expression in Rats Treated with Sennoside A, Senna Anthraquinones and Rhubarb Anthraquinones

Abstract: Senna and rhubarb are often used as routine laxatives, but there are differences in mechanism of action and potential side effects. Here, we studied metabolites of senna anthraquinones (SAQ), rhubarb anthraquinones (RAQ) and their chemical marker, sennoside A (SA), in a rat diarrhea model. In in vitro biotransformation experiments, SAQ, RAQ and SA were incubated with rat fecal flora solution and the metabolites produced were analyzed using HPLC. In in vivo studies, the same compounds were investigated for purg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The diarrhea was predominantly an acute toxic sign of damnacanthal, which was a dose-dependent manner. Since anthraquinone compounds have been widely used as stimulative laxatives such as senna anthraquinones and rhubarb anthraquinones [30] , the toxic effect may be caused by the anthraquinone properties of damnacanthal. It also has been reported that the purgative effect may be due to the presence of hydroxyl groups at the position of 1 and 8 (or 9) of the anthracene ring (a tricyclic aromatic ring) [31] .…”
Section: Resultsmentioning
confidence: 99%
“…The diarrhea was predominantly an acute toxic sign of damnacanthal, which was a dose-dependent manner. Since anthraquinone compounds have been widely used as stimulative laxatives such as senna anthraquinones and rhubarb anthraquinones [30] , the toxic effect may be caused by the anthraquinone properties of damnacanthal. It also has been reported that the purgative effect may be due to the presence of hydroxyl groups at the position of 1 and 8 (or 9) of the anthracene ring (a tricyclic aromatic ring) [31] .…”
Section: Resultsmentioning
confidence: 99%
“…Hematoxylin & Eosin staining (H&E) was carried out on the rat kidneys, livers, colons and stomachs. The procedure was described in our previous study [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…The immunohistochemistry staining was used to assess the expression of Aqp proteins on kidney tissues by using the method illustrated in our published study [ 12 ] Briefly, the dewaxed section was heated in citrate buffer with pH6 for 15 min, and blocked in 3 % of goat serum, followed to be incubated in primary antibody solution overnight at 4 °C. They were rabbit anti-aquaporin 1 (GB11310-1), anti-aquaporin 2 (GB112259), anti-aquaporin 3 (GB11395) and anti-aquaporin 4 (GB11529) with the dilution in 1:400.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that Rhei Radix et Rhizoma can lead to the downregulation of AQP3 and AQP4 expression, reduce the absorption of water in the colon, and increase the water content of the intestinal tract. Wang et al (2021) analyzed the metabolites of rhubarb anthraquinone and its chemical marker sennoside A in a Rhei Radix et Rhizoma diarrhea model. The results showed that rhubarb anthraquinone could downregulate the expression of various AQPs in the colon, kidneys, and liver of rats with diarrhea.…”
Section: Aqp Regulation By Tcms and Their Componentsmentioning
confidence: 99%